Pemberdayaan Masyarakat Melalui Konservasi Tanaman Obat untuk Menunjang Penyediaan Bahan Baku Produksi Jamu Tradisional - Parmin Parmin; Ani Rusilowati; Endah Fitriani Rahayu (Jurnal Pemberdayaan Masyarakat, 2022)
The Gogik Village Government has a medicinal plant conservation program that involves the community in cultivating various types of medicinal plants. Yards and gardens have been utilized to grow medicinal plants but there is no sustainability to products in the form of traditional herbal medicine. The purpose of the activity is to empower the community through the conservation of medicinal plants which are the local advantages of the village. Service activities use participatory methods in community empowerment. The participatory method used is environmental scanning which is an integral part of the process of empowering the community through building self-reliance with the strength of resources and products. The results of the activity found that there were five types of village superior medicinal plants. The community is actively involved starting from preparing the land, planting, caring for, and processing it into traditional herbal medicine. The conclusion is that Gogik Village community empowerment activities have been built from the awareness of the advantages of the natural potential. The development of local advantages through the conservation of herbal plants has provided real experience for the community to be more competitive.